2022
DOI: 10.3390/polym14142915
|View full text |Cite
|
Sign up to set email alerts
|

Novel Magnetic Elastic Phase-Change Nanodroplets as Dual Mode Contrast Agent for Ultrasound and Magnetic Resonance Imaging

Abstract: Recently, dual-mode imaging systems merging magnetic resonance imaging (MRI) and ultrasound (US) have been developed. Designing a dual-mode contrast agent is complex due to different mechanisms of enhancement. Herein, we describe novel phase change nanodroplets (PCNDs) with perfluoropentane encapsulated in a pre-polyglycerol sebacate (pre-PGS) shell loaded with polyethylene glycol (PEG)-coated iron oxide nanoparticles as having a dual-mode contrast agent effect. Iron oxide nanoparticles were prepared via the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 70 publications
1
2
0
Order By: Relevance
“…This curve is also evident due to the near-zero values of remanence magnetization (M r = 0.142 emu per g) and the squareness ratio of M r /M s = 0.004. The present study reports a coercivity value of 12.23 Oe and a saturation magnetization (M s ) of ∼33.2 emu 46 Another study of a similar material with particle size (50-300 nm) observed a coercivity value of 27 Oe and a M r of 2.2. 47 3.6 Inuence of different single parameters on nitrate removal from water…”
Section: Magnetic Characteristics Of Iecbssupporting
confidence: 60%
See 1 more Smart Citation
“…This curve is also evident due to the near-zero values of remanence magnetization (M r = 0.142 emu per g) and the squareness ratio of M r /M s = 0.004. The present study reports a coercivity value of 12.23 Oe and a saturation magnetization (M s ) of ∼33.2 emu 46 Another study of a similar material with particle size (50-300 nm) observed a coercivity value of 27 Oe and a M r of 2.2. 47 3.6 Inuence of different single parameters on nitrate removal from water…”
Section: Magnetic Characteristics Of Iecbssupporting
confidence: 60%
“…The present study reports a coercivity value of 12.23 Oe and a saturation magnetization ( M s ) of ∼33.2 emu per g. The given values are closely similar to the literature values of PEG-coated nanoparticles (<50 nm) with saturation magnetization of 23 emu per g and M r below 2 nm. 46 Another study of a similar material with particle size (50–300 nm) observed a coercivity value of 27 Oe and a M r of 2.2. 47…”
Section: Resultsmentioning
confidence: 97%
“…[7][8][9][10] However, when applied as ultrasound contrast agents (UCA), NBs commonly exhibit lower contrast signals compared to microbubbles due to the reduced scattering cross-section of a single bubble. 2,11,12 Efforts towards increasing the echogenicity of NBs have also been made in several studies, such as introducing a phase-change gas as the core of NBs when the NBs expand into more echogenic microbubbles under certain conditions, [13][14][15][16] or building a rattle-type mesoporous silica nanostructure with two contributing interfaces. 17,18 Theoretically, UCA echogenicity is expressed as the sum of the scattering cross-section for a single microbubble.…”
Section: Introductionmentioning
confidence: 99%